Towards biological control strategies for the bronze bug, Thaumastocoris peregrinus, on eucalyptus plantations in South America - Martinez, Gonzalo; Barbosa, Leonardo Rodrigues; Botto, Eduardo; Wilcken, Carlos Frederico [UNESP] (My University, 2014)
The bronze bug is an invasive Australian pest that has reached eucalypt production areas worldwide in <10 years. The fi rst record in South America was in 2005 in Argentina. Collaboration in the region towards a unifi ed strategy for the management of the bronze bug started soon after the dispersal of the pest into Brazil and Uruguay was confi rmed. Here, we present the main achievements of this collaboration in four main topics: 1) biology of the pest, 2) monitoring, 3) biological control, and 4) cooperative networks. Two mass rearing procedures have been implemented in the region with relative success, allowing basic biological studies on the pest. Continuous monitoring in the region for >5 years has provided a reasonable knowledge on seasonal patterns of T. peregrinus. Biological control strategies developed include the use of local natural enemies of T. peregrinus, the development of biopesticides, and the introduction of Cleruchoides noackae, an egg parasitoid of T. peregrinus from Australia. We review the main achievements in each country. Finally, a regional network of institutions, researchers, and students has strengthened in the region, providing a solid background for future collaboration.